Proceedings of the 3rd International Conference on Educational Management and Administration (CoEMA 2018) 2018
DOI: 10.2991/coema-18.2018.36
|View full text |Cite
|
Sign up to set email alerts
|

Empowering the Principal of Boarding House-Based Junior High School in East Java Province Indonesia

Abstract: This research aimed to know the level of empowerment of the principal of boarding house-based Junior High School in East Java, Indonesia. The research method used in this research was a descriptive quantitative method. This research was conducted in boarding house-based Junior High School in East Java Province, Indonesia. The samples were taken using a stratified random sampling technique. The research subjects were principals. The research instrument used was the questionnaire measuring the level of the empow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…DISCUSSION This study concludes that the application of the SSM-based human resource empowerment model is quite effective in influencing the learning leadership variable; change leadership; and spiritual leadership. This study is in line with the results of Kusumaningrum, et al (2018a) which concluded that the principal will be more empowered when the school adopts the SSM-based human resource empowerment model. Empowering the principal requires the ability of the school to treat the principal as the key person leading the school and not as a mere bureaucrat (Sudayat, 2014;Gunawan, et al, 2018).…”
Section: Figure 1 One-shot Case Studysupporting
confidence: 90%
See 2 more Smart Citations
“…DISCUSSION This study concludes that the application of the SSM-based human resource empowerment model is quite effective in influencing the learning leadership variable; change leadership; and spiritual leadership. This study is in line with the results of Kusumaningrum, et al (2018a) which concluded that the principal will be more empowered when the school adopts the SSM-based human resource empowerment model. Empowering the principal requires the ability of the school to treat the principal as the key person leading the school and not as a mere bureaucrat (Sudayat, 2014;Gunawan, et al, 2018).…”
Section: Figure 1 One-shot Case Studysupporting
confidence: 90%
“…Principal empowerment is related to the leadership and creativity possessed by the principal (Özarall, 2015;Gunawan, 2017). Therefore, the principal must be able to empower himself for the progress of the school (Kusumaningrum, et al, 2018a;Sultoni, et al, 2018;Pertiwi, et al, 2018).…”
Section: Figure 1 One-shot Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to direct value and ethical planting, of course, the planting of values and ethics also through various kinds of activities, such as congregational prayers and pengajian diniyah that examines the Qur'an and the existing traditions about ethic that must be owned by humans. Therefore, kyai is important to empower all the resources owned by boarding schools (Kusumaningrum, et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent leadership shows exemplary influences in others [2], [3], which means providing impetus to motivate him in building integrity, understanding in depth the principles of growing integrity [4]. Every leader must be able to understand the meaning and meaning of integrity that can be applied in his life.…”
Section: Introductionmentioning
confidence: 99%